Implementation of adaptive methods in early phase clinical trials - Petroni, Gina (Henry Stewart Talks, 2018)
Practical guidance on implementing adaptive designs in early-phase clinical trials, Essential protocol information that leads to acceptance of the design and directs implementation, Issues that need to be considered and addressed prior to starting an adaptive design, Examples & general check list on designing and implementing early-phase adaptive designs